PERTUMBUHAN DAN HASIL BEBERAPA KULTIVAR BAWANG MERAH PADA BERBAGAI DURASI GENANGAN - I Komang Sudarma; Tri Luchi Proklamita (Partner, 2017)
Shallot (Alium ascolonicum L.) is a very important horticultural commodity, but has a configuration in its cultivation on the condition of the flooded land. A tolerant cultivar for wetland conditions is needed. This research has been done in the field of Horticultural Laboratory of Agricultural Polytechnic State of Kupang from July to October 2017. Factors tried in this research is the factor of water logging duration and shallot cultivar factor. The research was design by split plot esign with the water logging duration as the main plot and the cultivar as the sub plot. The main plot consists of six level: without water logging (D0), 1 day water logging (D1), 2-day water logging (D2), 3-day water logging (D3), 4-day water logging (D4) and 5-day water logging (D5). The sub plot consists of 4 cultivar: Sabu (K1), Rote (K2), TTS (K3) and Bima (K4). The variables observed were: number of tillers, number of leaves, root length, leaf dry weight, total chlorophyll content and weight of dry yield. The data was analyzed by analysis of variance, and continued by BNJ test (5%). The results showed that the duration of the water logging affected the number of tillers, number of leaves, leaf dry weight, root length and weight of the dry bulb. While cultivars also affect the number of tillers, number of leaves, dry weight of leaves, and weight of dry bulb, but do not affect to root length. While the total chlorophyll content of shallot affected by the interaction between the duration of water logging and cultivars. The results also showed a decrease in the number of tillers, number of leaves, leaf dry weight and weight of the dry yield in the duration of the 5-day water logging. While the length of the roots decreased after given inundation more than 3 days. The best cultivars in this study were the Bima cultivars that produced a dry yield of 56.28 g.Â Key word: Growth, yield, water logging duration and shallot cultivar